A cultural biography of Mantombi Matotiyana and Maxanjana Mangaliso : two contemporary African musicians - Lewis, Mary Christine (Stellenbosch : University of Stellenbosch, 2012)
Thesis (MMus) -- University of Stellenbosch, 2001.